Implementing ecologically-inspired landscape design retrofits within exurban neighborhoods - Leyva, Alfonso Santiago (Kansas State University, 2016)
Since the mid-1960s a paradigm shift in environmental values has been initiated in Europe, parts of the United States, and many other parts of the world, culminating in a focus on green infrastructure based development (Ahern et al., 2007b). During the 1980s and 1990s sustainability and landscape ecology began to be important aspects of landscape architecture education and practice (Swaffield, 2002; Ahern, 2005). The effort to create sustainable cities, neighborhoods, and sites is making a difference in urban areas, which is very important since global census data shows that a majority of the earth’s population now lives in urban settlements (United Nations, 2014). Personal and cultural values reveal an environmental consciousness and strong interest in sustainability in many communities (Peiser & Hamilton, 2012). Nevertheless, many developments associated with landscape construction seem to implement few, if any, sustainable practices as new neighborhoods in many parts of the U.S. are developed. This study develops a modified ecological approach and applies this outlook to an existing exurban neighborhood in Manhattan, Kansas. Quantitative and qualitative research includes: 1) a review of relevant literature and precedent studies; 2) a multi-tiered site analysis informed by landscape ecology principles; and 3) surveys of local homeowners regarding landscape maintenance practices and their willingness to install more ecologically appropriate landscapes. It is anticipated that sustainable design considerations for Lee Mill Heights and nearby areas will emerge to inform future neighborhood retrofits, helping move existing subdivisions towards more ecologically appropriate patterns and processes.
Keywords: Landscape architecture; Sustainable design; Landscape retrofits; Lee Mill Heights